Characterisation of six novel A-subunit mutations leading to congenital factor XIII deficiency and molecular analysis of the first diagnosed patient with this rare bleeding disorder - Schroeder, Verena; Meili, Esther; Cung, Trinh; Schmutz, Peter; Kohler, Hans P. (Thrombosis and Haemostasis, 2006)
In 1960, the first case report on factor XIII deficiency was published describing a seven-year-old Swiss boy with a so far unknown bleeding disorder. Today, more than 60 mutations in the factor XIIIA- and B-subunit genes are known leading to congenital factor XIII deficiency. In the present study, we describe six novel mutations in the factor XIII A-subunit gene. Additionally, we present the molecular characterisation of the first described patient with congenital factor XIII deficiency. The six novel mutations include a small deletion, Glu202 del G, leading to a premature stop codon and truncation of the protein, and a splice site mutation at the exon 10/intron 10 boundary, +1G/A, giving rise to an incorrect spliced mRNA lacking exons 10 and 11. The remaining four mutations are characterised by the single amino acid changes Met159Arg, Gly215Arg, Trp375Cys, and His716Arg, and were expressed in COS-1 cells. Antigen levels and activity of the mutants were significantly reduced compared to the wild-type. The patient described in 1960 also shows a single amino acid change, Arg77Cys. Structural analysis of all mutant enzymes suggests several mechanisms leading to destabilisation of the protein.
Keywords: Coagulation factor XIII; congenital FXIII deficiency; FXIII Asubunit gene